2-Azabutadiene complexes of rhenium(i): S, N-chelated species with photophysical properties heavily governed by the ligand hidden traits. Issue 8 (10th February 2021) - Schlachter, Adrien; Juvenal, Frank; Kinghat Tangou, Rodolphe; Khatyr, Abderrahim; Guyon, Fabrice; Karsenti, Paul-Ludovic; Strohmann, Carsten; Kubicki, Marek M.; Rousselin, Yoann; Harvey, Pierre D.; Knorr, Michael
Abstract : The S, N -coordination of azabutadienes onto  fac -Re(CO)3 X species creates moderately emissive complexes, which exhibit ultrafast and multiphasic deactivation kinetics of both their singlet and triplet (MLCT/ILCT) excited states. Abstract : The reaction of [Re(CO)3 (THF)(μ-Br)]2 or [Re(CO)5 X] (X = Cl, Br, I) with the diaryl-2-azabutadienes [(RS)2 CC(H)–NCAr2 ] containing two thioether arms at the 4, 4-position forms the luminescent S, N -chelate complexes fac -[(OC)3 ReX{(RS)2 CC(H)–NCAr2 }] (1a–h ). The halide abstraction by silver triflate converts [(OC)3 ReCl{(PhS)2 CC(H)–NCPh2 }] (1c ) to [(OC)3 Re(OS(O)2 CF3 ){(PhS)2 CC(H)–NCPh2 }] (1j ) bearing a covalently bound triflate ligand. The cyclic voltammograms reveal reversible S^N ligand-centred reduction and irreversible oxidation waves for all complexes. The crystal structures of nine octahedral complexes have been determined along with that of (NaphtylS)2 CC(H)–NCPh2 (L6 ). A rich system of weak non-covalent intermolecular secondary interactions through CH⋯X(Cl, Br)Re, CH⋯O, CO⋯π(Ph), CH⋯πCO, CH⋯O and CH⋯S contacts has been evidenced. The photophysical properties have been investigated by steady-state and time-resolved absorption (fs transient absorption, fs-TAS) and emission (ns-TCSPC and ps-Streak camera) spectroscopy in 2-MeTHF solution at 298 and 77 K. The emission bands are composed of either singlet (450 < λ max < 535 nm) and/or triplet emissions (at 77 K only, λ max < 640 nm, or appearing as a tail at λ > 600 nm), which decay in a multiexponential manner for the fluorescence (short ps ( i.e. F < 1.9 ns at 298 and 77 K) and monoexponentially for the phosphorescence (4.0 < τ P < 7.0 ns at 77 K). The fs-TAS data reveal the presence of 2 to 4 transient species decaying in four narrow time windows (generally 125–165 fs, 370–685 fs, 3–6 ps, 30–45 ps). The complexity of these kinetics was explained by studying the photophysical behaviour of ligand L6 . Its behaviour is the same as the complexes thus indicating that the ligand dictates the kinetic traits of the Re-species, except for the triplet emission as L6 is not phosphorescent. The triplet lifetime (4.0 < τ P < 7.0 ns) is considered very short but not unprecedented. Furthermore, the nature of the lowest energy excited states of these chelate compounds and L6 has been addressed using DFT and TDDFT calculations and been assigned to metal-to-ligand (MLCT) and/or intraligand charge-transfer (ILCT).